Phanerozoic general circulation model results and quantitative climate data for Australia - Frakes, L. A.; Barron, E. J. (Australian journal of earth sciences, 2001)
Quantitative data bearing on Phanerozoic climates of Australia are summarised and comparisons are made with the predictions of atmospheric general circulation models over 12 time slices from the Silurian to the Miocene. Summaries of the model derived mean temperature and precipitation conditions are given individually for each of four regions (southeast, northeast, southwest and northwest). Model results provide the means of estimating climate conditions in many cases, but there is fair agreement between the two approaches in most cases in which data are available. On model results, the southeast experienced winter freezing conditions from the Permian through until the middle Cretaceous and was consistently the coolest of the four regions, in part because of its proximity to the pole, but also because it was the site of elevated terrain throughout most of the Phanerozoic. It also tended to be among the wettest parts of Australia over this time and was subject to frequent winter storms. The northeast, in contrast, was often the warmest part of the continent, although strong seasonality and freezing winter temperatures were common during the Mesozoic and Palaeozoic. Strong seasonality (>30°C contrast between winter and summer) also apparently characterised most of the record for the southwest region, except for the Tertiary, part of the Jurassic, and the Early Palaeozoic. Together with the southeast, this region experienced the most intense effects of winter, especially in the Triassic. Strong seasonality also affected the northwest region through much of the Palaeozoic and Mesozoic and, interestingly, the highest summer temperatures on the continent are predicted for the southwest for most of the time slices studied. The models used today are imperfect but, nonetheless, offer a means of prediction and will perhaps stimulate the gathering of quantitative data in a continent where information is hard to come by and for which not much has yet been presented.